Characteristics of nonfatal occupational injuries among U.S. workers with and without disabilities. Issue 2 (February 2015) - Shi, Junxin; Gardner, Stephen; Wheeler, Krista K.; Thompson, Meghan C.; Lu, Bo; Stallones, Lorann; Xiang, Huiyun
<x xml:space="preserve">Abstract</x> Background Workers with disabilities have a higher risk of nonfatal occupational injuries than workers without disabilities. The characteristics of these injuries are not well described. Methods Using 1997–2011 National Health Interview Survey (NHIS) data, we compared the nonfatal occupational injuries sustained by U.S. workers with and without disabilities. Results Overexertion or strenuous movements and falls accounted for 56.7% of all occupational injuries in workers with disabilities, compared with 45.6% in workers without a disability. Workers with disabilities were more frequently injured in the lower extremity (32.3% vs. 26.6%) or torso (22.9% vs. 16.9%). Workers with disabilities sustained more unspecified injuries (13.5% vs. 7.9%) and fewer open wound injuries (15.7% vs. 24.2%) than their counterparts without a disability. Conclusions U.S. workers with disabilities had a higher rate of occupational injuries and these injuries tended to be more severe and were more likely to be caused by overexertion/ strenuous movement or falls. Am. J. Ind. Med. 58:168–177, 2015. © 2015 Wiley Periodicals, Inc.